Penambahan Spirulina Pada Poto Poto Untuk Meningkatkan Kualitas Produk Pangan di Kab. Sinjai - Zaraswati Dwyana; Nur Haedar Nur Haedar; Moh. Ivan Azis; Rosana Agus; Muh. Ruslan Umar (Universitas Hasanuddin, 2019)
Spirulina is a marine phytoplankton that is a microalgae that has great potential in life, one of which is food, because the nutritional coverage contained in this marine phytoplankton includes proteins, carbohydrates, vitamins, minerals, essential fatty acids DHA and EPA so that it can be used as an alternative nutritious food. . The purpose of this activity is to training on inovative snack “Poto Poto Sinjai”, how to make Spirulina in Bongki Village, Sinjai Regency. The method used in this activity consisted of a location survey and the production of snack from Spirulina . The implementation phase of the activity using counseling methods and training on the benefits of Spirulina as nutritious food and making snack Spirulina. The results of the implementation of this activity were the increase in participants' knowledge about snack Spirulina, as a highly nutritious snack. The results of the knowledge improvement test show that there is a fairly good increase in knowledge of the snack Spirulina innovation products and the results of the organoleptic test show that preference for taste, aroma, texture and color shows good results.